High calcium scores in coronary CT angiography: Effects of image post-processing on visualization and measurement of coronary lumen diameter - Sun, Zhonghua; Ng, Curtise Kin Cheung (American Scientific Publishers, 2014)
High calcium scores due to heavy calcification in the coronary artery wall present challenge to accurately diagnose coronary artery stenosis due to blooming artifacts associated with the severe calcification. This has been reported to significantly reduce specificity when compared to the diagnostic value in patients with low calcium scores. In this study, we tested a number of image post-processing approaches in a sample patient with high calcium scores (>400) with the aim of determining the appropriate technique for reduction of the effect of high calcium scores on the visualization of coronary artery wall and measurement of the coronary lumen diameter. Our results showed that the image post-processing approach, default ImageJ sharpen function improved the visualization of coronary artery with measured coronary lumen diameter similar to that measured with invasive coronary angiography. Our preliminary findings highlight the potential value of using image post-processing techniques for minimizing artifacts due to high calcium scores, although further studies with more robust data analysis and evaluation are warranted.